2021
DOI: 10.1177/10790632211051682
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Sexual Aggression in UK Male University Students: An Empirical Assessment of Prevalence and Psychological Risk Factors

Abstract: University-based sexual aggression is an international public health issue; however, to date, there have been no formal assessments of the prevalence or psychological indicators associated with the proabuse behaviors of the most common perpetrators at UK universities: heterosexual male students. To facilitate the development of effective primary prevention interventions for domestic students who have sexually harmed, we assess across two empirical studies ( Ns = 259 and 295) the psychological risk factors asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 81 publications
2
17
0
1
Order By: Relevance
“…Each of these expressions was evident within this study, although worryingly, victims' accounts revealed that acts of more overt, extreme violence, and escalations in behaviour occurred more frequently than would be expected. Hales and Gannon (2022) have observed similar trends to our findings, with their research into sexual violence highlighting that students commit acts of sexual violence more frequently than their non-student counterparts. As a guiding lens for theorising targeted hostility, Perry (2001) draws attention to the role of power, whereby offenders attempt to (re)assert relative positions of dominant and subordinate identities.…”
Section: Discussionsupporting
confidence: 91%
“…Each of these expressions was evident within this study, although worryingly, victims' accounts revealed that acts of more overt, extreme violence, and escalations in behaviour occurred more frequently than would be expected. Hales and Gannon (2022) have observed similar trends to our findings, with their research into sexual violence highlighting that students commit acts of sexual violence more frequently than their non-student counterparts. As a guiding lens for theorising targeted hostility, Perry (2001) draws attention to the role of power, whereby offenders attempt to (re)assert relative positions of dominant and subordinate identities.…”
Section: Discussionsupporting
confidence: 91%
“…In other words, those who engaged in penetrative RSB were less likely to commit only nonpenetrative sexual assault. Of note, earlier research on university-based sexual offending has supported the role of deviant and risky sexual fantasies as a precursor to sexual offending [79,80]. Consistently, sexual risk-taking behavior was found to be a significant predictor of subsequent sexual offending behavior in more recent studies [34,35,39].…”
Section: Discussionmentioning
confidence: 72%
“…To deal with this problem and retain all T1 participants in the sample, appropriate procedures for dealing with missing data were employed. Finally, other established risk factors of sexual aggression perpetration were not addressed in the study, such as rape myth acceptance, 61 hostile attitudes toward women, 62,63 or peer acceptance of sexual aggression. 64…”
Section: Discussionmentioning
confidence: 99%